Dispensable Role of Mitochondrial Fission Protein 1 (Fis1) in the Erythrocytic Development of Plasmodium falciparum - Mulaka Maruthi (American Society for Microbiology, 2020)
ABSTRACT Malaria remains a huge global health burden, and control of this disease has run into a severe bottleneck. To defeat malaria and reach the goal of eradication, a deep understanding of the parasite biology is urgently needed. The mitochondrion of the malaria parasite is essential throughout the parasite’s life cycle and has been validated as a clinical drug target. In the asexual development of Plasmodium spp., the single mitochondrion grows from a small tubular structure to a complex branched network. This branched mitochondrion is divided at the end of schizogony when 8 to 32 daughter cells are produced, distributing one mitochondrion to each forming merozoite. In mosquito and liver stages, the giant mitochondrial network is split into thousands of pieces and daughter mitochondria are segregated into individual progeny. Despite the significance of mitochondrial fission in Plasmodium, the underlying mechanism is largely unknown. Studies of mitochondrial fission in model eukaryotes have revealed that several mitochondrial fission adaptor proteins are involved in recruiting dynamin GTPases to physically split mitochondrial membranes. Apicomplexan parasites, however, share no identifiable homologs of mitochondrial fission adaptor proteins with yeast or humans, except for Fis1. Here, we investigated the localization and essentiality of the Fis1 homolog in Plasmodium falciparum, PfFis1 (PF3D7_1325600), during the asexual life cycle. We found that PfFis1 requires an intact C terminus for mitochondrial localization but is not essential for parasite development or mitochondrial fission. The dispensable role of PfFis1 indicates that Plasmodium contains additional fission adaptor proteins on the mitochondrial outer membrane that could be essential for mitochondrial fission. IMPORTANCE Malaria is responsible for over 230 million clinical cases and ∼half a million deaths each year. The single mitochondrion of the malaria parasite functions as a metabolic hub throughout the parasite’s developmental cycle (DC) and also as a source of ATP in certain stages. To pass on its essential functions, the parasite’s mitochondrion needs to be properly divided and segregated into all progeny during cell division via a process termed mitochondrial fission. Due to the divergent nature of Plasmodium spp., the molecular players involved in mitochondrial fission and their mechanisms of action remain largely unknown. Here, we found that the only identifiable mitochondrial fission adaptor protein that is evolutionarily conserved in the Apicomplexan phylum, Fis1, it not essential in P. falciparum asexual stages. Our data suggest that malaria parasites use redundant fission adaptor proteins on the mitochondrial outer membrane to mediate the fission process.